Standards in wildlife forensic science, with a focus on non‐human DNA analysis - Frankham, Greta J.; Ogden, Rob; Baker, Barry W.; Ewart, Kyle M.; Johnson, Rebecca N.; Kuiper, Irene; Lindquist, Christina D.; Moore, M. Katherine; Ndiaye, Arame; Webster, Lucy M. I. (Animal genetics, 2025)
For genetic data to be used in forensic casework, it has to be produced within a controlled environment that follows strict quality standards. However, recent reviews have suggested that wildlife forensic laboratories are behind in the development and adherence to appropriate standards for casework. This paper will address these concerns by documenting the standards that have been produced, highlighting the systems of assessment and competency testing available, and reviewing the status of validated reference genetic databases. Networks of dedicated wildlife forensic scientists across the globe, represented in part by the author list for this paper, illustrate the strides taken to build capacity in this field, and an ongoing commitment to present quality wildlife forensic evidence in court.